Identification of hypothetical duplicate accessions of plums (Prunus domesticaL.) within the Slovene Plant Gene Bank Collection using molecular markers - Šiško, Metka (Agricultura (Maribor), 2016)
The main goal of the Slovene Plant Gene Bank is preservation, maintenance and evaluation of traditional cultivars and other useful genotypes. The Faculty of Agriculture and Life Sciences houses among other plant materials also numerous accessions of plums (Prunus domestica L.). Duplicates among 15 accessions were studied using six microsatellite primer pairs. These microsatellite markers revealed an average of 7.67 alleles per locus, and a range of 4 to 10 different alleles per locus. The genetic distances between studied accessions were calculated using the Dice coefficient to form a dendrogram. The six SSRs were found to be adequate for differentiating among genotypes within the collection. Among the analysed accessions no duplicates were found.
Keywords: duplicate accessions; gene bank; genska banka; mikrosatelitski markerji; plums; podvojene akcesije; Prunus domestica; slive; SSR markers